Mama Cookies Enterprise / Ismayanie Hidayu Ismail... [et al.] - Ismail, Ismayanie Hidayu; Hazmy, Dylisya Caryn; Muwaaz, Nurul Husna; Othman, Nor Shakinah (2012)
‘Mama Cookies Enterprise’ is the name of our company is created for people who love to eat healthy cookies. It also represents our company motto that is “Good, Delicious, and Healthy. We will make our customers especially who had diseases and cannot take sweet cookies can enjoy our cookies. In taking a first step into business we choose Seberang Perai Tengah as the location of our business activity because it is surrounding by various type or people from infant until baby boomers. In this area, there are public university and polythecnic such as UiTM Permatang Pauh and Polytechnic Seberang Prai. We choose here because student would prefer affordable prices since they do not have their own pocket money yet. Beside that, this location also surrounding by useful facilities and we can use in our business operation. The main product that we use in this cookie is Nestum and Oat together with chocolate chip and other garnishing. We already know that Oat and Nestum is for person who had a cholesterol disease. That is the reason we produce cookies special for them to have a bite even though they have to take care of their body. ‘Mama Cookies Enterprise is managing by four qualified managers, Ismayanie Hidayu Bt. Ismail (General Manager), Dylisya Caryn Bt. Hazmy (Marketing Manager), Nurul Husna Bt. Muwaaz (Operational Manager), and Nor Shakinah Bt. Othman (Financial Manager). Our business commencement is on ist Janua°' 2013. Our industry profile is healthy cookies and everyone can have a bite. The reason we venture into food business is because we know that various organization are supporting new entrepreneur in this industry such as SME Corporation Malaysia. Other than that the raw material is available here in Malaysia and it easy for us to produce our product. We can ensure our target market that our products will satisfied their needs and wants because we deliver affordable cookies to eat anytime and anywhere they want to. We hope that our product will well know and had a topic of conversation to others.